Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1097/fjc.0b013e31829f0c1b
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Tolerability of Azilsartan in Obese Insulin-Resistant Mice with Left Ventricular Pressure Overload

Abstract: Angiotensin II receptor blockers (ARBs) are used widely for the treatment of heart failure. However, their use in obese and insulin-resistant patients remains controversial. To clarify their potential efficacy in these conditions, we administered azilsartan medoxomil (azilsartan), a prodrug of an angiotensin II receptor blocker to mice fed a high-fat diet (HFD) with left ventricular (LV) pressure overload (aortic banding). LV fibrosis (hydroxyproline), cardiac plasminogen activator inhibitor-1 (PAI-1; a marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
0
9
0
1
Order By: Relevance
“…In the soleus muscle of KKAy, mRNA expression levels of TNFα, MCP1, and Nox2 were increased and IRS-1 was decreased, but this overexpression was not attenuated by either candesartan cilexetil or azilsartan. It has been shown that azilsartan reduced left ventricular hypertrophy, cardiac fibrosis, plasminogen activator inhibitor-1 (PAI-1; a marker of profibrosis) in aortic banding mice fed high-fat diet [55], indicating that azilsartan may exert favorable biological effects in non-diabetic obese insulin-resistant condition, which shares a common mechanism such as enhanced ROS/inflammation signals with the current model.…”
Section: Discussionmentioning
confidence: 99%
“…In the soleus muscle of KKAy, mRNA expression levels of TNFα, MCP1, and Nox2 were increased and IRS-1 was decreased, but this overexpression was not attenuated by either candesartan cilexetil or azilsartan. It has been shown that azilsartan reduced left ventricular hypertrophy, cardiac fibrosis, plasminogen activator inhibitor-1 (PAI-1; a marker of profibrosis) in aortic banding mice fed high-fat diet [55], indicating that azilsartan may exert favorable biological effects in non-diabetic obese insulin-resistant condition, which shares a common mechanism such as enhanced ROS/inflammation signals with the current model.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ZDF and GK rats usually exhibited a significant increase of the septum and LVPW thicknesses, reduced LV diastolic and systolic diameters, enlarged cardiomyocyte volume, and higher expression rates of ANP, in spite of the fact that contractile function was frequently preserved [ 10 , 12 , 28 31 ]. Finally, the limited body of evidence on diet-induced T2DM rather pointed hypertrophy as the only morphological alteration constantly present, independently of its high-fat of high-sugar diet origin [ 13 , 32 34 ]. However, a recent work reported no difference in heart weight and cardiomyocyte size but overexpression of ANP, BNP, and β -MHC after a 16-week-long high-fat diet [ 35 ].…”
Section: Main Models Of Diabetic Cardiomyopathy (Dcm)mentioning
confidence: 99%
“…Thus, it has been suggested that all diabetic patients with BP greater than 130/80 mm Hg should begin ACEI treatment unless contraindicated. 15,16,17,18,19,20,21 Our study indicated a limited congruency to this principle.…”
Section: Discussionmentioning
confidence: 64%